Vagal Schwannoma: A Rare Parapharyngeal Tumour - Kamath, Panduranga M (J Clin Diagn Res, 2016)
Among the parapharyngeal tumours, salivary gland tumours are the commonest, followed by schwannomas, which are slow growing benign tumours. Half of the parapharyngeal schwannomas originate from the vagus. Complete surgical excision is the treatment of choice. We hereby present two cases of parapharyngeal schwannomas, one which had presented as an intraoral mass and the other as a swelling in the neck. The first case, a 57-year-old female patient complained of a slowly increasing swelling in the left side of the throat since 3 months, associated with pain and dysphagia. In the Contrast Enhanced CT scan of the neck, a well-defined cystic lesion with central enhancing solid components (4cm X 4.5cm X 3cm) was seen in the left parapharyngeal region. The second case, a 39-year-old male patient complained of a painless, gradually increasing swelling below the lobule of the right ear since one month. Examination revealed a solitary, nontender, firm and mobile swelling of 2cm X 2cm below the lobule of the right ear. In Contrast Enhanced CT scan of the neck, an enhancing lesion was seen involving the right parapharyngeal space, post-styloid compartment. Both the patients underwent trans-cervical surgical excision. Vagal nerve schwannoma is rare. The majority of the cases present with a slow growing neck swelling without neurological deficit. Complete surgical excision of the tumour is important to prevent recurrence.